Integrating AI Waste-Sorting Technology into Entrepreneurship Education: An Experimental Study on Student - Sharfina Puteri Amima; Rizky Mega Arini; Riyadatul Muthmainnah; Annisa Tri Hidhayati; Rizky Aldi Setianda; Monry Fraick Nicky Gillian Ratumbuysang (Al-Qalam Institue, 2026)
This study aims to evaluate the effectiveness of integrating AI-based waste-sorting technology into entrepreneurship education to enhance students’ cognitive literacy and entrepreneurial self-efficacy. The study employed a quantitative pre-experimental method using a One-Group Pretest–Posttest design involving 29 high school students. Data were collected through cognitive literacy tests, Likert-scale questionnaires, and observations of system performance. The findings indicate a substantial improvement in students’ cognitive literacy, with mean scores increasing from 38.62 in the pretest to 84.14 in the posttest, achieving an N-Gain score of 0.74 categorized as high. Students also demonstrated highly positive perceptions of the learning innovation, reflected in perceived usefulness (91.0%) and entrepreneurial interest (90.4%). Although the AI waste-sorting system achieved a classification accuracy of 63.8%, it effectively promoted students’ awareness of sustainable practices and encouraged entrepreneurial thinking related to environmental issues. The study implies that AI technology can function as a sociotechnical educational tool that transforms environmental challenges into innovation opportunities and supports the development of sustainability-oriented entrepreneurial competencies among students.